2020
DOI: 10.7554/elife.55911
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase knockouts modify transcription, CAG instability and nuclear pathology in Huntington disease mice

Abstract: Somatic expansion of the Huntington's disease (HD) CAG repeat drives the rate of a pathogenic process ultimately resulting in neuronal cell death. Although mechanisms of toxicity are poorly delineated, transcriptional dysregulation is a likely contributor. To identify modifiers that act at the level of CAG expansion and/or downstream pathogenic processes, we tested the impact of genetic knockout, in HttQ111 mice, of Hdac2 or Hdac3 in medium-spiny striatal neurons that exhibit extensive CAG expansion and exquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 109 publications
(227 reference statements)
0
5
0
Order By: Relevance
“…Relationships between HDACs, HATs and repeat instability appear to be complex, however. For example, knockdown of HDAC9 promoted, rather than suppressed, CAG expansion in the cultured astrocyte model [76], and HDAC inhibitors promoted contractions in a selectable human cell-based assay [91]. In S. cerevisiae, loss of function of different HDACs either enhanced or suppressed CAG instability [75,228], with CAG stability being dependent on activities of both HDACs and HATs that control levels of H4 acetylation [228].…”
Section: Cis Elements Chromatin and Post Translational Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships between HDACs, HATs and repeat instability appear to be complex, however. For example, knockdown of HDAC9 promoted, rather than suppressed, CAG expansion in the cultured astrocyte model [76], and HDAC inhibitors promoted contractions in a selectable human cell-based assay [91]. In S. cerevisiae, loss of function of different HDACs either enhanced or suppressed CAG instability [75,228], with CAG stability being dependent on activities of both HDACs and HATs that control levels of H4 acetylation [228].…”
Section: Cis Elements Chromatin and Post Translational Modificationmentioning
confidence: 99%
“…These genetic data are supported by the suppression of instability upon treatment with the Class I/II HDAC inhibitor trichostatin A (TSA) [ 203 ]. Genetic knockout of either Hdac2 or Hdac3 in MSNs of Htt Q111 knock-in mice moderately suppressed striatal expansions [ 91 ]. The impact of Hdac3 knockout in this model is consistent with the expansion-suppressing effect of a selective HDAC3 inhibitor [ 227 ].…”
Section: Cis Elements Chromatin and Post Translational Modificationmentioning
confidence: 99%
“…SETD2 recruits MutSα (MSH2-MSH6) to chromatin (Huang and Li, 2020); however, the opposing directions of effects targeting Setd2 and Msh6 do not obviously support such a role in vivo . CBP, SETD2 and SETDB1 may alternatively act via post-translational modification of DNA repair proteins themselves (Kovalenko et al ., 2020; Williams et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…30,33 Subsequent analyses revealed that the striatal specific expansions occurred predominantly in the medium spiny neurons that are the primary target of neurodegeneration in HD. 34,35 Given that longer inherited alleles cause an earlier age at onset, and that in nearly all the model systems greater pathologic effects are observed with longer CAGs, it seems logical to assume that somatic expansion of the CAG repeat in HD may contribute toward the progressive nature and tissue specificity of the symptoms. Consistent with this hypothesis, it was shown that in HD individuals with the same inherited repeat length, those with greater somatic expansion in the cortex showed earlier disease onset.…”
Section: Somatic Expansion In Hdmentioning
confidence: 99%